Validitas Media Pembelajaran Pop Up Book Terintegrasi Ayat Al-Quran Pada Materi Sistem Organisasi Kehidupan Kelas VII SMP - Fira Asrianita; Najmiatul Fajar; M Haviz; Rina Delfita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The biology teacher at the school is constrained by learning media, the media used is limited such as power points, videos, and charts. In terms of students, it is known that students aremore enthusiastic when teachers use learning media such as videos, power points, and chapters than when teachers only use books as learning media. This results in a lack of reading interest of students and also the ability to think critically and creatively of students which causes students to lack understanding of science material, especially biology. Development or research and development with a model referring to the 4-d development model. The result of study, at the validation stage carried out by 3 validators consisting of 1 lecturer and 2 teachers who teach at the school. The result of the validation of learning media obtained an average value of 92.12% categorized as very valid from the aspects of didactic requirements, contruction requirements, technical requirements, language and integrated pop up book components of Al-qur’an verses.